Web-based Financial Reporting Disclosure: Evidence from selected banks in the Kingdom of Saudi Arabia (KSA) - Adel M. Sarea (Journal of Central Banking Theory and Practice, 2020)
With insights drawn from legitimacy theory undergirding perceived relative factors expected to influence the level of Web-Based Financial Reporting Disclosure (WBFRD), this paper sheds light on the level of the Web-Based Financial Reporting Disclosure (WBFRD) in selected banks in the KSA in 2017. Several gauges exist for measuring the level of transparency and disclosure practices. As a result of the unique characteristics of the banking sectors operating in the KSA under the Sharia-compliant (Islamic) law, however, the researcher eschewed employing Standard & Poor's Transparency and Disclosure checklist. Accordingly, the researcher designed a 90-item index based on metrics identified in previous studies. The selected banks in the KSA evince a high level of Web-Based Financial Reporting Disclosure (WBFRD) on the order of 76%. Regression analysis indicates a positive association between the independent variables Bank Size, Bank age, and Profitability on one side, and the dependent variable Web-Based Financial Reporting Disclosure (WBFRD) on the other side.
Keywords: G20; G21; 330; Web-Portal; Web-Based Financial Reporting Disclosure; Banking sector; Legitimacy theory; KSA